KAJIAN WAKTU SIMPAN KAROTEN KAPANG ONCOM MERAH (NEUROSPORA SP) YANG DIPRODUKSI PADA MEDIA TONGKOL JAGUNG - Kenyamu, Mardalena; Mappiratu, Mappiratu; Nurakhirawati, Nurakhirawati (Univ. Tadulako, 2014)
The investigation about study of the shelf lifeof red oncom mold carotene (Neurosporasp) from corn cob media has been done. This study aimed to determine the shelf life of red oncom mold carotene in capsules packaging at various storage temperatures. It was done by applying two phases of research i.e the production red oncommold and the determination of shelf life at the temperature of 50?C and 60?C. Carotene levels were determined using spectrophotometric method. The resultshowedthat carotene shelf life at a temperature of 50?C and 60?C were 44.31 and 34.05 daysrespectively. The Changed of carotene quality in capsule packaging followedthe zero-order kinetics. The calculation result shoewd Q10 value was 1.3 and the shelf life at variouse temperatures was determined based on the value of Q10. Storage at room temperature caused the shelf life for74.80 days.